SUMBER DAYA DAN KARAKTERISTIK ENDAPAN PASIR BESI DI CIHERAS, KABUPATEN TASIKMALAYA: RESOURCES AND CHARACTERISTICS OF IRON SAND DEPOSITS IN CIHERAS, TASIKMALAYA DISTRICT - Teuku Ishlah; Suwahyadi; Dwi Nugroho Sunuhadi (Buletin Sumber Daya Geologi, 2023)
Iron is a metal commodity that is widely used in human civilization, and is now used as a raw material for making steel and a mixture of raw materials for cement. Therefore, research activities on iron sand deposits are still needed, especially in ex-mining areas that are interesting for re-examination, because increase of metal price, so decrease the cut off grade for iron sand concentrate mining and the possibility of the presence of other high value minerals. The research location is located in Ciheras Village, Cipatujah District, including Block Ciheras-1, Block Ciheras-2, and Block Cikalong, Cikadu Village, Cikalong District, Tasikmalaya Regency, West Java Province. The aim of this research is to determine the availability, quality and estimation of inferred resources for iron sand deposits. The research used geological mapping methods, and sampling using a hand auger at a distance of 400 meters between drilling points in the direction of the base line and 40 meters in the direction of the cross line. A total of 71 points were drilled to a depth of between 2.0 meters to 4.0 meters and samples of iron sand were taken for laboratory analysis including specific gravity (BJ), magnetic percentage (MD), sieve/grain fraction analysis, grain mineralogy analysis, XRF , AAS, and colorimetry. The calculation results for the iron sand resources of the Ciheras-1 Block are 257,138 tonnes, the Ciheras-2 Block is 512,199 tonnes, and the Cikalong Block is 491,970 tonnes, bringing the total to 1,261,308 tonnes. Average percentage of magnetism in the Ciheras-1 Block; 24.02%, Ciheras-2 Block; 14.7%, and Cikalong Block; 8.01%. These iron sand deposits come from rocks and ash from volcanic eruptions which are transported by river water to estuaries and deposited on beaches. High economic value elements in the form of Titanium and Vanadium in beach sand deposits in the research area whose levels and occurrence are comparable to the element Fe.